2007
DOI: 10.1016/j.jsurg.2007.01.018
|View full text |Cite
|
Sign up to set email alerts
|

Contributions of surgical residents to patient satisfaction: Impact of residents beyond clinical care

Abstract: Purpose:Little is known about the relationship between resident performance and patient satisfaction. To this end, this institution added housestaff-specific questions to Press-Ganey surveys administered to patients. This study sought to investigate the impact residents have on patient's overall rating of care provided compared with faculty and nursing staff. Methods: Between March 2005 and April 2006, half of all discharged patients randomly received Press-Ganey surveys, including questions on the following c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(17 citation statements)
references
References 0 publications
0
16
0
1
Order By: Relevance
“…Similarly, Thi et al. (2002) and Resnick et al. (2008) found that the level of satisfaction of the patients who were treated on surgical wards was high.…”
Section: Discussionmentioning
confidence: 88%
“…Similarly, Thi et al. (2002) and Resnick et al. (2008) found that the level of satisfaction of the patients who were treated on surgical wards was high.…”
Section: Discussionmentioning
confidence: 88%
“…Similarly, according to some studies with patients related to satisfaction with nursing care, the patients treated on surgical wards reported greater satisfaction than those treated on the medical wards (Thi et al. 2002, Resnick et al. 2008, Fındık et al.…”
Section: Discussionmentioning
confidence: 95%
“…It has also been shown that residents contribute to patient satisfaction in addition to the care they provide [26]. In order to ensure the best hands-on training for residents while maintaining a high standard-of-care for patients, residency program directors must balance multiple interests.…”
Section: Discussionmentioning
confidence: 99%